Effectiveness of Interpersonal Leadership for Engagement and Task Performance of Nurses. (May 2020) - Habib, Nazia; Awan, Sajid Hussain; Naveed, Shaheryar; Shoaib Akhtar, Chaudhry
Transformational leadership has been studied as an essential trait for nurse leaders in the past; however, there is a dearth of studies on interpersonal leadership which is a combined construct of transformational leadership and interactional justice. The main objective of this article was to examine the relationship between interpersonal leadership and task performance. A cross-sectional research design was adopted for this study. 700 questionnaires were circulated among nurses from 14 major hospitals across the country. Out of these, 336 nurses replied. The final usable sample size was 283 full-time nurses, out of which 91.8% were female. The online and paper-based instruments were floated twice, at different timings with different cover letters to avoid common method bias. Nurses perceive that interpersonal leadership can significantly enhance their task performance. Similarly the study also found significant mediation of work engagement in the positive relationship between interpersonal leadership and task performance. Moreover, there was no significant difference between public and private sector nurses about interpersonal leadership and its relationship with work engagement and task performance. Interpersonal leadership has been found as significantly and positively effective toward work engagement and task performance of nurses working both in public and private sector hospitals. The results establish that by adopting the interpersonal leadership style, a nurse leader can enhance the work engagement of her followers. The study suggests that interpersonal leadership should be adopted as a total concept in nurse management to achieve better results in terms of work engagement and task performance.